The archaeology and epigraphy of Indus writing - Wells, Bryan K., (Archaeopress archaeology., 2015)
'The Archaeology and Epigraphy of Indus Writing' is a detailed examination of the Indus script. It presents new analysis based on an expansive text corpus using revolutionary analytical techniques developed specifically for the purpose of deciphering the Indus script. This exploration of Indus writing examines the structure of Indus text at a level of detail that has never been possible before.